THE ANALYSIS OF STRUCTURE OF INNOVATIVE CAPACITY OF THE ENTERPRISE ON THE EXAMPLE OF THE AVIATION INDUSTRY - N. Arsenjeva; L. Mikhailova; A. Sazonov (Вестник университета)
It is shown that as one of the main and signicant components of eective functioning of the hi-tech enterprise the high percent of an intellectual component in its structure acts. Indicators by means of which components of innovative potential can be estimated are considered. On the basis of the carried-out assessment of the key components which are a part of innovative potential the modied formula of calculation of the expected size of the prot got from sale of hi-tech production which the enterprise makes independently is oered.